'Painting a path to wellness': Correlations between participating in a creative activity group and improved measured mental health outcome - Caddy, L.; Crawford, Frances; Page, A. (Blackwell Publishing Ltd, 2012)
Responding to a call for quantitative outcome evidence about the therapeutic relationship between creative activity and mental health, this study examined the mental health outcomes of inpatients participating in art- and craft-based creative therapies at a private psychiatric hospital over a 5-year period. The creative activity group sample (n = 403) improved from admission to discharge across four different psychometric measures with moderate to strong mean effect sizes. Reductions from pre- to post-treatment in both self-reported and clinician-rated symptoms are clearly demonstrated for the creative activity group participant sample. Research findings establish that participation in creative activity has potential benefits for people experiencing mental health problems